2018
DOI: 10.3390/su10072330
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Intensity, Economic Development and Energy Factors in 19 G20 Countries: Empirical Analysis Based on a Heterogeneous Panel from 1990 to 2015

Abstract: Abstract:The increasing global climate problem caused by excessive carbon emissions results in global carbon emission reduction governance becoming a top priority and requires close international coordination. Group of Twenty (G20) is gradually becoming the leading agency of global carbon emission reduction governance, but the unbalanced development among G20 countries has hindered the full play of G20's role. Thus, this paper aims to examine the interrelationships among economic development mode, economic dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
(61 reference statements)
0
2
0
1
Order By: Relevance
“…Their study found no long-run relationship between crude oil prices and economic growth, however, they found evidence of short-run associations between the variables. Li et al (2018) investigated the interrelationship of carbon emission intensity, economic development and energy factors in 19 out of the G20 countries, using a panel heterogeneity data from 1990 to 2015. By conducting panel cointegration using the three-panel root test, they found the existence of long-run equilibrium among the variables.…”
Section: Review Of Research Literaturementioning
confidence: 99%
“…Their study found no long-run relationship between crude oil prices and economic growth, however, they found evidence of short-run associations between the variables. Li et al (2018) investigated the interrelationship of carbon emission intensity, economic development and energy factors in 19 out of the G20 countries, using a panel heterogeneity data from 1990 to 2015. By conducting panel cointegration using the three-panel root test, they found the existence of long-run equilibrium among the variables.…”
Section: Review Of Research Literaturementioning
confidence: 99%
“…Secara umum, refleksi komitmen G20 terhadap perencanaan pembangunan nasional dapat memberikan pemahaman mengenai "peran dan efektivitas KTT G20 terhadap keseimbangan pertumbuhan ekonomi" (Kantorowicz, 2020b), dan 'kapasitas' (Cooper, 2015;Ikenberry & Mo, 2013b) serta 'kontribusi' (Agarwal & Whalley, 2020;Faghih & Sazegar, 2019) negara dalam mengimplementasikan agenda pembangunan global. Selain peran dan efektivitas G20, refleksi komitmen terhadap rencana pembangunan nasional juga dapat mengidentifikasi keselarasan antara kepentingan nasional terkait pembangunan dengan agenda global tertentu seperti perubahan iklim (Damodaran, 2015;Malpass, 2021), energi (Ghosh, 2015;Li et al, 2018;Mehra & Datt, 2015;Wang & Dong, 2021), dan anti korupsi (Kobets, 2021).…”
Section: Kerangka Analisisunclassified
“…In today's globalized and industrialized world, energy efficiency appears to only be achievable though the gradual but steady transition to a low-carbon economy. Many governments across the globe have set up strict targets for tackling climate change, decreasing the use of carbon fuels, reducing the emissions of carbon dioxide (CO 2 ) and other greenhouse gases, as well as increasing the share of renewable energy in total energy generation [1].…”
Section: Introductionmentioning
confidence: 99%